2020
DOI: 10.1111/basr.12191
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of sustainable supply chain initiatives: Empirical evidence from the S&P 500

Abstract: Prior research on sustainable supply chain management (SSCM) has almost exclusively focused on environmental aspects (GSCM—green supply chain management) and the study of its external drivers and consequences. Framing our study within the “strategy‐conduct‐performance” paradigm, we consider the focal firm's role in the implementation of sustainable supply chain initiatives, social as well as environmental. We use data on the S&P 500 Index retrieved from Bloomberg, including variables for two relevant focal fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
(92 reference statements)
1
14
0
Order By: Relevance
“…Using the same instrumental variable approach as before, we find that female board representation does not significantly affect financial performance, but it does have a positive and significant impact on environmental and social performance. These findings are in line with the broader literature on the subject: Evidence on the relationship between female board representation and financial performance is mixed (e.g., Post & Byron, 2015), whereas the positive effect of boardroom gender diversity on firms' environmental and social performance is fairly well‐established (e.g., Arayssi et al, 2016; Crichton et al, 2021; Sebastianelli & Tamimi, 2020; Shaukat et al, 2016). These results are particularly relevant in light of the recent push for global sustainability reporting standards and ESG disclosure regulations (Caroom, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Using the same instrumental variable approach as before, we find that female board representation does not significantly affect financial performance, but it does have a positive and significant impact on environmental and social performance. These findings are in line with the broader literature on the subject: Evidence on the relationship between female board representation and financial performance is mixed (e.g., Post & Byron, 2015), whereas the positive effect of boardroom gender diversity on firms' environmental and social performance is fairly well‐established (e.g., Arayssi et al, 2016; Crichton et al, 2021; Sebastianelli & Tamimi, 2020; Shaukat et al, 2016). These results are particularly relevant in light of the recent push for global sustainability reporting standards and ESG disclosure regulations (Caroom, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Previous GSCI research neglect the possible interaction between various forms of GSCI ( Lo et al, 2018 ; Wong et al, 2020 ), while others fail to recognize the effect of technological advancement and organizational capabilities on GSCI and organizational performance ( Wu, 2013 ; Al-Ghwayeen and Abdallah, 2018 ). Few researches has concentrated on the connection between GSC initiatives and organizational performance, e.g., ( Green et al, 2012 ; Yu et al, 2014 ; Cousins et al, 2019 ; Sebastianelli and Tamimi, 2020 ). However, the consideration of these concepts is not clear enough, especially in developing countries where the concept of “go-green” is not mature enough.…”
Section: Introductionmentioning
confidence: 99%
“…However, the consideration of these concepts is not clear enough, especially in developing countries where the concept of “go-green” is not mature enough. Meanwhile, the literature has found that leveraging capabilities within an organization can enhance organizational effectiveness, increase organizational value, reduce external pressure, and lead to better organizational performance ( Zhu et al, 2010 ; Sebastianelli and Tamimi, 2020 ; Shahzad et al, 2020 ; Wang et al, 2020 ; Kitsis and Chen, 2021 ). Therefore, this study attempts to analyze the relationship between GSCI and organizational performance from the perspective of GI, combined with dynamic capability theory, so as to better explain this process.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some of them were targeted at determination of the antecedents of inter-firm supply chain cooperation in the implementation of sustainability initiatives. Sebastianelli and Tamimi (2020) with the use of data on the S&P 500 Index retrieved from Bloomberg found that higher levels of diversity and independence of the focal firm's board of directors, as well as the focal firm's involvement in internal green policies and practices has a positive impact on the implementation of green and social supply chain initiatives. They also revealed that the researched companies are more likely to have implemented both types of supply chain practices -environmental and social, then just one of them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These approaches can also have a significant impact on the extent to which links in the supply chain cooperate when implementing sustainable development initiatives. Some of the previous studies were targeted at determination of the antecedents of inter-firm supply chain cooperation in the implementation of sustainability initiatives, revealing, for example, that the internal imple-mentation of sustainable development initiatives, governance board characteristics (Sebastianelli & Tamimi, 2020), existence of various bonds in relationships (Tran et al, 2021), or management and work organisation methods (Nath & Agrawal, 2020) impact their implementation at the supply chain level. However, to my best knowledge, no research has verified whether companies can have different approaches to cooperation in the supply chain when implementing sustainable development initiatives, i.e., whether they generally strive to cooperate in this area or usually try to implement them on their own.…”
Section: Introductionmentioning
confidence: 99%